Pobreza y bosques en America Latina: una agenda de accion - Kaimowitz, D. (Plan de Accion Forestal para Guatemala (PAFG), 2002)
Approximately 25 millon people live in the main forested regions of Latin America. The forestry sector there directly provides two or three million jobs and perhaps another three or four million people work in related activities. Many poor households use fuelwood, hunt wild animals, and benefit from the environmental services forests provide. A pro-poor forest agenda for the region should include greater tenure rights over forests for small farmers, indigenous people, and local communities, fewer and simpler forestry regulations, programs that provide credit and information about markets and technology, better working conditions for forestry workers, and efforts to bring peace to forested regions.